Optimizing the Performance of Multinational Business Organizations through Cross-Cultural Communication Management: Review and Recommendations - Yovi Bathesta; Wibawa Prasetya; Alfilonia Harwinda; Kamal Kamal; Nabila Alda Yuniar (Warta Ikatan Sarjana Komunikasi Indonesia, 2024)
Multinational companies face challenges in understanding and managing cultural differences. Cross-cultural communication becomes a crucial issue that affects organizational performance. This research aims to investigate the cross-cultural communication problems faced by multinational companies, focusing on identifying the factors influencing cross-cultural communication, their impact on company performance, and strategies that can be adopted to address these challenges. The research method used is a literature review involving critical analysis of journals and related research findings sourced from Google Scholar. Previous studies utilized should highlight various factors affecting cross-cultural communication, including language differences, cultural norms, stereotypes, and differences in non-verbal communication patterns. The research findings indicate that multinational companies need to adopt a holistic and proactive approach in managing cross-cultural communication, such as employee training to enhance cross-cultural awareness, strategic approaches in recruiting personnel with diverse cultural backgrounds, and the development of inclusive communication policies sensitive to cultural differences. Failure to manage cultural differences can lead to conflict, decreased productivity, and failure to achieve business goals. Academic suggestions include the need for further research to explore effective communication strategies in different cultural contexts. Additionally, longitudinal studies can help understand the dynamics of cross-cultural communication evolution in the long term. Practical suggestions include the need for management commitment to create an inclusive work environment that supports all team members, regardless of their cultural backgrounds. Companies should also integrate cross-cultural communication training into their employee development programs to enhance communication effectiveness in an increasingly complex global context.